2006
DOI: 10.1111/j.1875-595x.2006.tb00075.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health behaviour of children and adults in urban and rural areas of Burkina Faso, Africa

Abstract: Health authorities should strengthen the implementation of oral disease prevention and health promotion programmes rather than traditional curative care. Community-oriented essential care and affordable fluoride toothpaste should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
103
7
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 18 publications
14
103
7
9
Order By: Relevance
“…Sobre un total de 28 puntos considerados para evaluar el nivel de conocimientos de salud bucodental, el puntaje mínimo obtenido en las respuestas fue de quince puntos. Estos resultados son similares a los obtenidos en un estudio previo [19] y difieren de trabajos realizados en Carolina del Norte, EEUU [27], China [3], Arabia Saudita [28], Jordania [29] y África [30] que reportaron en general un conocimiento de salud bucodental bajo en la población encuestada.…”
Section: Discussionunclassified
“…Sobre un total de 28 puntos considerados para evaluar el nivel de conocimientos de salud bucodental, el puntaje mínimo obtenido en las respuestas fue de quince puntos. Estos resultados son similares a los obtenidos en un estudio previo [19] y difieren de trabajos realizados en Carolina del Norte, EEUU [27], China [3], Arabia Saudita [28], Jordania [29] y África [30] que reportaron en general un conocimiento de salud bucodental bajo en la población encuestada.…”
Section: Discussionunclassified
“…No entanto, os dados mostram que, entre os estudantes da escola pública, houve uma porcentagem signifi cati va de indivíduos que responderam ter retornado ao denti sta em um tempo maior que um ano. Talvez isso possa ser explicado pelo poder aquisiti vo da população da insti tuição pública, ou mesmo seu nível educacional [15][16][17][18] . O moti vo da últi ma visita ao denti sta para os estudantes da escola privada demonstrou maior consciência preventi va desses, se comparados com os da escola pública.…”
Section: Discussionunclassified
“…This condition was also influenced by the proper frequency of tooth brushing, as well as the use of tooth brushing devices and methods. 11 In a study conducted by Nurhidayat et al in 2012 showed that in Indonesia, the people ignorance on the importance of oral health care was still high. This condition proofed by the rate of Indonesian people who was not brushing their teeth was as much as 22.8%, and from 77.2% of the people were brushing their teeth only 8.1% of the people were brushing their teeth on the right frequency and time as recommended by dentists.…”
Section: Discussionmentioning
confidence: 99%